2018
DOI: 10.1111/ane.12966
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival of Swedish glioblastoma patients treated according to Stupp

Abstract: Survival significantly improved after the implementation of the Stupp regimen in the study region of Sweden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
7
9
0
Order By: Relevance
“…Our study con rms previous ndings of a considerably poorer prognosis in butter y glioblastoma compared to glioblastoma in general, where population-based studies observed a median overall survival of nine to 11 months [22][23][24][25]. A median overall survival of 5.9 months in our cohort was comparable to the results from previous butter y glioblastoma studies, with median survival ranging from 3.2 to 5.9 months [4,5,8].…”
Section: Survivalsupporting
confidence: 90%
“…Our study con rms previous ndings of a considerably poorer prognosis in butter y glioblastoma compared to glioblastoma in general, where population-based studies observed a median overall survival of nine to 11 months [22][23][24][25]. A median overall survival of 5.9 months in our cohort was comparable to the results from previous butter y glioblastoma studies, with median survival ranging from 3.2 to 5.9 months [4,5,8].…”
Section: Survivalsupporting
confidence: 90%
“…Our study con rms previous ndings of a considerably poorer prognosis in butter y glioblastoma compared to glioblastoma in general, where population-based studies observed a median overall survival of nine to 11 months [23][24][25][26]. A median overall survival of 5.5 months in our cohort was comparable to the results from previous butter y glioblastoma studies, with median survival ranging from 3.2 to 5.9 months [4,5,8].…”
Section: Survivalsupporting
confidence: 90%
“…Our study shows that the benefits of GTR, followed by CRT with temozolomide seen in clinical trials and recent population studies 4,23,31 are also applicable in an unselected population. It should be emphasised that the survival difference between cohort A and B cannot only be explained by the implementation of CRT with temozolomide since other treatment regimens have been introduced in the later years, such as postoperative MRI and the use of 5‐ALA.…”
Section: Discussionsupporting
confidence: 54%
“…Approximately 1200 cases with primary brain tumours are diagnosed yearly in Sweden 1 . Glioblastoma (GBM) is the most frequent tumour diagnosis with an incidence of 4/100.000 and the most devastating tumour with a median overall survival (OS) of less than 15 months 2‐4 …”
Section: Introductionmentioning
confidence: 99%